Resting-State Functional Correlates of Social Cognition in Multiple Sclerosis: An Explorative Study - Bisecco, Alvino; Altieri, Manuela; Santangelo, Gabriella; Di Nardo, Federica; Docimo, Renato; Caiazzo, Giuseppina; Capuano, Rocco; Pappacena, Simona; d’Ambrosio, Alessandro; Bonavita, Simona; Trojsi, Francesca; Cirillo, Mario; et al. (Frontiers in Behavioral Neuroscience, 2020)
Social cognition includes mental operations essential for functional social interactions, and several studies revealed an impairment of social cognition abilities in patients with Multiple Sclerosis (MS). These deficits have been related to global and focal gray matter atrophy as well as microstructural white matter damage. Although some studies reveal a correlation between social cognition and task-based functional magnetic resonance imaging (MRI), no studies to date have explored the association between brain resting-state functional connectivity (RS-FC) abnormalities and several measures of social cognition in MS. The aim of this explorative study was to assess the contribution of RS-FC abnormalities of major brain networks to social cognition in MS patients. Clinical, neuropsychological, and MRI data were collected from 41 non-depressed and cognitively preserved relapsing-remitting MS patients (mean disease duration = 8.8 ± 8.2 years; median Expanded Disability Status Scale = 1.5, range 0–6.5) and 25 matched healthy controls (HCs). The ToM Pictures Sequencing Task (TMPS) and the Reading the Mind in the Eyes Task were employed to evaluate social cognition. All participants underwent a structural MRI and RS functional MRI 3T protocol. Regional gray matter atrophy was measured, and FCs of the default mode (DMN), right and left fronto-parietal, executive (EN), salience, cerebellar, and limbic (LN) networks were evaluated by independent component analysis (ICA). Differences on TMPS were found between MS patients and HC (MS < HC). In the MS group, associations were found between right middle temporal gyrus FC (in the DMN) and reciprocity subscale of TMPS, posterior cingulate cortex (PCC) FC (in the DMN) and first-order false-belief subscale of TMPS, cingulate gyrus FC (in the EN) and TMPS as well as reciprocity subscale of TMPS, and right superior temporal gyrus (in the LN) and reciprocity subscale of TMPS. All detected RS-FC changes did not co-localize with regional gray matter atrophy. The results suggest an association between social cognition and RS-FC changes of DMN, EN, and LN in MS. Future studies should further explore the possible adaptive or maladaptive mechanisms of these FC abnormalities in MS.